ENVIRONMENTAL POLICY, SUSTAINABLE DEVELOPMENT, PUBLIC ADMINISTRATION, COMPARATIVE STUDY, INDONESIA, GERMANY - Khairunnisa, Rahma; Aminullah (International Journal of Multidisciplinary Reseach, 2026)
Environmental policy and sustainable development have become central issues in modern governance as ecological pressures from development activities continue to intensify. This article aims to analyze and compare environmental policy and sustainable development in Indonesia and Germany using a descriptive–comparative approach based on a literature review. Indonesia, as a developing country with abundant natural resources, faces serious challenges in environmental management, while Germany, as a developed country, is widely recognized as a pioneer in environmental policy and sustainable energy transition. Drawing on classical public administration literature, international academic journals, and official government documents from both countries, this article examines policy frameworks, institutional arrangements, policy instruments, and the implications of environmental policy for sustainable development. The findings indicate that differences in political context, economic structure, and institutional capacity significantly influence policy effectiveness. This study is expected to contribute conceptually and practically to the development of environmental policy in Indonesia through comparative policy learning.